Dipolar hole-blocking layers for inverted perovskite solar cells: effects of aggregation and electron transport levels - Butscher, Julian; Sun, Qing; Wu, Yufeng; Stuck, Fabian; Hoffmann, Marvin; Dreuw, Andreas; Paulus, Fabian; Hashmi, A. Stephen K.; Tessler, Nir; Vaynzof, Yana (JPhys materials, 2020)
Herein, we report on the synthesis and investigation of two triazino-isoquinoline tetrafluoroborate electrolytes as hole-blocking layers in methylammonium triiodide perovskite photovoltaic devices with fullerene electron extraction layer. We find that increasing the thickness of the dipolar hole-blocking layer results in a gradual increase in the open-circuit voltage suggesting that aggregation of the molecules can enhance the dipole induced by the layer.
Gesehen am 24.03.2021